Urgensi Scientific Research Programme Imre Lakatos bagi Pengembangan Studi Islam - Moh Tamtowi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
According to Lakatos, the development of science occurs continuously. He rejected the revolution in the development of science. Here he differs with Thomas S. Kuhn. Lakatos proposed a model of scientific research Programmes. Scientific research program consists of two main elements, namely the hard core and protective belt. The hard-core is a core principal of the program, while the protective belt serves to protect the hard core from the criticism and attacks. Falsification occurs only in the protective belt teritory, rather than on the hard core. This ideas is rejecting the opinion of Karl Popper. Scientific research program has benefits and significance in Islamic studies, namely: first, the history of the development and growth of religious knowledge can be explained very well. Second, conformity with the purpose of maintaining the hard-core of Islam (al-Qur’an). The revision and reformulation occurs only in the sciences and analytical tools of Islamic.